ChemInform Abstract: Synthesis of Functionalized 2‐Isoxazolines as Three‐Dimensional Fragments for Fragment‐Based Drug Discovery. Issue 41 (October 2015) - Tran, Ngoc Chau; Dhondt, Heleen; Flipo, Marion; Deprez, Benoit; Willand, Nicolas
Abstract In situ generated nitrile oxides undergo 1, 3‐dipolar cycloaddition with alkenes to give 2‐isoxazoline derivatives.